2015
DOI: 10.3389/fmats.2015.00062
|View full text |Cite
|
Sign up to set email alerts
|

Shape Memory Polymer Nanofibers and Their Composites: Electrospinning, Structure, Performance, and Applications

Abstract: Shape memory polymers (SMPs) have been defined as a kind of smart materials under great investigation from academic research to industry applications. Research on SMPs and their composites now incorporates a growing focus on nanofibers which offers new structures in microscopic level and the potential of enhanced performance of SMPs. This paper presents a comprehensive review of the development of shape memory polymer nanofibers and their composites, including the introduction of electrospinning technology, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 58 publications
0
27
0
Order By: Relevance
“…Electrospun systems are well known for their peculiar advantages, such as: a finely controlled micro‐/nanometric fiber orientation and porosity; large surface‐to‐volume ratio; versatility, flexibility, and ease of fiber production; relatively low cost and high production rates; well‐known performances as scaffolds for tissue engineering. By providing them also stimuli‐responsive features, it is possible to obtain multifunctional systems that may be employed as innovative drug delivery systems, protective clothing for environmental applications, and membranes for selective filtration, photovoltaic cells, electrolytic batteries . Further, biomedical applications may be greatly favored, to ultimately obtain systems and devices for the regenerative medicine and minimally invasive surgery (such as vascular stents, scaffolds for bone regeneration), and for this reason most of the research on shape memory nonwovens belongs to this field .…”
Section: Introductionmentioning
confidence: 99%
“…Electrospun systems are well known for their peculiar advantages, such as: a finely controlled micro‐/nanometric fiber orientation and porosity; large surface‐to‐volume ratio; versatility, flexibility, and ease of fiber production; relatively low cost and high production rates; well‐known performances as scaffolds for tissue engineering. By providing them also stimuli‐responsive features, it is possible to obtain multifunctional systems that may be employed as innovative drug delivery systems, protective clothing for environmental applications, and membranes for selective filtration, photovoltaic cells, electrolytic batteries . Further, biomedical applications may be greatly favored, to ultimately obtain systems and devices for the regenerative medicine and minimally invasive surgery (such as vascular stents, scaffolds for bone regeneration), and for this reason most of the research on shape memory nonwovens belongs to this field .…”
Section: Introductionmentioning
confidence: 99%
“…As the temperature exceeding the glass or melting transition, the recovery actuation will be triggered. Rather than bulk film, the Shape Memory Effect (SME) employed in fibers at the micro- or nano-scale probably promotes the research of textiles in situations of immediate control due to the high porosity [ 157 ]. In an early study, PCL based shape memory PU fibrous mat was produced by electrospinning, which showed excellent shape recovery with 98% and 80% shape fixity [ 158 ].…”
Section: Hybrid Smart Electrospun Fibersmentioning
confidence: 99%
“…were obtained using phenolphthalein, aromatic ketone, imide, amide, and nitrile group containing phenols or amines. [83][84][85][86][87][88][89][90] Likewise, benzoxazines from renewable reagents were synthesized, successfully. [91,92] It should be mentioned that naphthols can be used to replace phenols and several naphthoxazines were also synthesized accordingly.…”
Section: Strategies In Designing Phenolics For Service Toolsmentioning
confidence: 99%